PTU-111 Determining Ceiling Of Care In Decompensated Cirrhosis – Right Decisions, Right People, Right Time. (9th June 2014) - Hudson, B; Morrison, H; Gordon, FH; McCune, CA; Collins, PL; Portal, AJ
Abstract : Introduction: Decisions to initiate intensive care measures in patients with decompensated liver cirrhosis are often controversial, with mortality approaching 90% in cirrhotics with 3 organ failure. The 2013 NCEPOD report 'Measuring the Units', which examined alcoholic liver disease-related deaths, nonetheless found that 31% of those who stood to benefit from higher level care did not receive it. We studied escalation of care decisions and subsequent outcomes in cirrhotic patients with organ failure. Methods: Consecutive patients with a diagnosis of cirrhosis admitted over a 90 day period in 2013 to the Bristol Royal Infirmary were studied. Severity of liver disease was assessed using Childs-Pugh and UKELD. Organ failure was defined using SOFA (Sequential Organ Failure Assessment) criteria. Care escalation/ withdrawal decisions were assessed in respect to timing, seniority and expertise of decision maker. Outcome measures of ICU admission, mortality and instigation of palliative care were recorded. Results: 42 admissions for 37 patients (ages 16–79, 79% male, 81% related to alcohol, 22% Childs A, 54% Childs B, 24% Childs C) were scrutinised. 30% had suffered variceal haemorrhage on, or during, admission. Of 17 patients admitted in organ failure, ICU admission was requested on 8 occasions (6 by a hepatologist, 1 during out of hours admission, 1 following out of hours deterioration). Escalation plans had been discussed with ICU prior to the point of clinical deterioration in 50%. 3 patients were accepted to ICU for mechanical ventilation, of which none survived. 1 patient was accepted in principle but improved clinically. 4 patients were declined ICU admission on grounds of poor prognosis, all of whom had alcoholic cirrhosis. Of this group all required non-invasive ventilation, with 75% surviving to discharge. Across the entire cohort 55% of hepatologist led "for full escalation if required" decisions were agreed in principle with ICU. 33% of ICU decisions to withdraw care were discussed with the referring hepatologist. Of the 7 patients who died overall, 4 were on an end of life tool with appropriate palliative measures in place. Conclusion: The high survival rates in patients refused intensive care, and high mortality amongst mechanically ventilated patients highlight the complexities of predicting outcomes in this population. Despite this, discussions between hepatology and ICU regarding ceiling and withdrawal of care often did not occur until the point of clinical deterioration, risking delays to esclation of care or appropriate palliation. Strategies to ensure early escalation decisions involving senior hepatologists and intensivists should be developed to ensure appropriate care is afforded to all cirrhotic patients in a timely fashion. Disclosure of Interest: None Declared.